Anticholinergic burden and most common anticholinergic-acting medicines in older general practice patients - Cedilnik-Gorup, Eva (Zdravstveno varstvo, 2018)
Introduction: Anticholinergic burden in older adults has been correlated with cognitive decline, delirium, dizziness and confusion, falls and hospitalisations. Nevertheless, anticholinergic-acting medications remain commonly prescribed in up to a third of older adults in primary care population. Our aim was to study the anticholinergic burden in older adults in Slovenian ambulatory setting and explore the most commonly involved medications which could be avoided by the physicians. Methods: A cross-sectional study was conducted in 30 general practices in Slovenia as part of a larger trial. Data on prescribed medications were collected for randomly chosen adults of over 65 years of age visiting general practice, who were taking at least one regularly prescribed medication. Anticholinergic burden was calculated using Duran%s scale and Drug Burden Index. Results: Altogether, 622 patients were included, 356 (57.2%) female, average age of 77.2 (%6.2), with an average of 5.6 medications. At least one anticholinergic medication was present in 78 (12.5 %) patients. More than half (N=41, 52.6%) of anticholinergic prescriptions were psychotropic medications. Most common individual medications were diazepam (N=10, 1.6%), quetiapine (N=9, 1.4%) and ranitidine (N=8, 1.3%). Conclusions: Though the prevalence of anticholinergic medications was low compared to international research, the most commonly registered anticholinergic prescriptions were medications that should be avoided according to guidelines of elderly prescriptions. It would be probably clinically feasible to further decrease the anticholinergic burden of older adults in Slovenian primary care setting by avoiding or replacing these medications with safer alternatives.
Keywords: aged; ambulante družinske medicine; anticholinergic burden; antiholinergično breme; general practice; inappropriate prescribing; neprimerno predpisovanje zdravil; starostniki